Film festivals : history, theory, method, practice - Kredell, Brendan; Loist, Skadi; Valck, Marijke de (Routledge, 2016)
The last decade has witnessed an explosion of interest in film festivals, with the field growing to a position of prominence within the space of a few short years. Film Festivals: History, Theory, Method, Practice represents a major addition to the literature of the topic, offering an authoritative and comprehensive introduction to the area.- Resumé vydavatel